2021
DOI: 10.3389/fnbeh.2021.725091
|View full text |Cite
|
Sign up to set email alerts
|

Variable Response of Norepinephrine Transporter to Traumatic Stress and Relationship to Hyperarousal

Abstract: The noradrenergic systems play a key role in stress triggered disorders such as post-traumatic stress disorder (PTSD). We hypothesized that traumatic stress will alter expression of norepinephrine transporter (NET) in locus coeruleus (LC) and its target brain regions which could be related to hyperarousal. Male Sprague-Dawley rats were subjected to single prolonged stress (SPS) and several weeks later the LC was isolated. NET mRNA levels in LC, determined by RT-PCR, displayed variable response with high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Trauma and/or long-term stressors might produce dysregulation in noradrenergic neural networks, which has been implicated in the pathophysiology of PTSD as the source of hyperarousal clusters (Nwokafor et al 2021). Neuroimaging findings in PTSD patients revealed that behavioral and autonomic hyper-responsiveness is induced by a strong phasic noradrenergic stimulus originating in the LC (Naegeli et al 2018).…”
Section: Adrenergic Neural Network and Ptsdmentioning
confidence: 99%
“…Trauma and/or long-term stressors might produce dysregulation in noradrenergic neural networks, which has been implicated in the pathophysiology of PTSD as the source of hyperarousal clusters (Nwokafor et al 2021). Neuroimaging findings in PTSD patients revealed that behavioral and autonomic hyper-responsiveness is induced by a strong phasic noradrenergic stimulus originating in the LC (Naegeli et al 2018).…”
Section: Adrenergic Neural Network and Ptsdmentioning
confidence: 99%
“…The norepinephrine (NE) system has wide projections from the locus coeruleus to the cerebral cortex, and is involved in the regulation of various brain functions and behaviors such as arousal, memory acquisition, attention, vigilance, and response to stress [ 10 ]. NE is synthesized by the amino acid tyrosine through a sequential reactions catalyzed by tyrosine hydroxylase, DOPA decarboxylase and dopamine β hydroxylase (DβH).…”
Section: Introductionmentioning
confidence: 99%